Nasalance values for syllables produced by Brazilian Portuguese speakers - Marino, Viviane Cristina de Castro [UNESP]; Cardoso, Vanessa Moraes [UNESP]; Ramos, Renata Giorgetto [UNESP]; Dutka, Jeniffer de Cássia Rillo (FapUNIFESP (SciELO), 2016)
Purpose: This study aimed to determine nasalance values for syllables produced by Brazilian Portuguese speakers of different ages and gender. Methods: Nasalance scores were collected for 14 syllables (10 orals and 4 nasals) using Nasometer II 6400. The participants were 245 Brazilian Portuguese speakers (121 males and 124 females), both genders, divided into four age groups: 57 children, 61 adolescents, 65 young adults and 62 adults. Results: Nasalance scores for nasal syllables were higher than for oral syllables. For both, oral and nasal syllables, nasalance scores were higher for vowel /i/ than for /a/. Across all syllables, the females' nasalance scores were higher than males, with most of this difference attributed to the oldest age group where females mean nasalance was three points higher than males. Conclusion: Values obtained demonstrated nasalance scores variation according to gender, particularly for the adult group and for the syllables tested.
Keywords: Acoustics; Adolescent; Adult; Children; Speech; Speech Acoustics